2009
DOI: 10.1016/j.clinimag.2008.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and etiology of solitary hot spots in the pelvis at whole-body positron emission tomography/computed tomography imaging

Abstract: Purpose-To determine the frequency and etiology of a single hypermetabolic focus within the pelvis with no other areas of increased 18-fluorodeoxyglucose (FDG) uptake in the reminder of the whole body in an oncological population.Method and Materials-We retrospectively examined the first 700 whole-body PET/CT scans performed at our institution for baseline staging or follow-up of cancer and identified all patients with a solitary focus of increased FDG uptake in the pelvis. All available medical records and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In our study, in addition to local recurrences, other malignant lesions, such as peritoneal carcinomatosis (n = 7) and an incidental uterine carcinoma (n = 1), showed increased FDG uptake. Although PET is regarded as being highly sensitive, it shows increased FDG uptake in other benign conditions, such as inflammation; it can also show physiologic uptake in muscle, fat, and bowel tissue [ 2 , 9 ]. In our study, 13 patients showed a variety of hypermetabolic, benign etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in addition to local recurrences, other malignant lesions, such as peritoneal carcinomatosis (n = 7) and an incidental uterine carcinoma (n = 1), showed increased FDG uptake. Although PET is regarded as being highly sensitive, it shows increased FDG uptake in other benign conditions, such as inflammation; it can also show physiologic uptake in muscle, fat, and bowel tissue [ 2 , 9 ]. In our study, 13 patients showed a variety of hypermetabolic, benign etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is uncommon but not rare in pre- and post-menopausal women. Abundant cellularity and hormonal dependency without malignant transformation are responsible for such uptake [ 4 , 5 ]. Another question raised by the PET/CT scan results was whether or not these lesions were NFBs or even a malignant transformation of a uterine NFB.…”
Section: Discussionmentioning
confidence: 99%
“…Klinische Studien haben aufgezeigt, dass eine inzidentelle fokal oder diffus erhöhte [ 18 F]FDG-Anreicherung im Becken mit einer Inzidenz von 1,1 % zu finden ist [37,38].…”
Section: Beckenunclassified